Methanol-Driven Oxidative Rearrangement of Biogenic Furans – Enzyme Cascades vs. Photobiocatalysis - Jäger, Christina; Bruneau, Cloé; Wagner, Philip K.; Prechtl, Martin H. G.; Deska, Jan (Frontiers in Chemistry, 2021)
The oxidative ring expansion of bio-derived furfuryl alcohols to densely functionalized six-membered O-heterocycles represents an attractive strategy in the growing network of valorization routes to synthetic building blocks out of the lignocellulosic biorefinery feed. In this study, two scenarios for the biocatalytic Achmatowicz-type rearrangement using methanol as terminal sacrificial reagent have been evaluated, comparing multienzymatic cascade designs with a photo-bio-coupled activation pathway.